2022
DOI: 10.1111/liv.15368
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the humoral and cellular response after the thirdCOVID‐19 vaccination in patients with autoimmune hepatitis

Abstract: Background & Aims To explore the humoral and T‐cell response to the third COVID‐19 vaccination in autoimmune hepatitis (AIH). Methods Anti‐SARS‐CoV‐2 antibody titers were prospectively determined in 81 AIH patients and 53 healthy age‐ and sex‐matched controls > 7 days (median 35) after the first COVID‐19 booster vaccination. The spike‐specific T‐cell response was assessed using an activation‐induced marker assay (AIM) in a subset of patients. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Compared to the antibody level of primary immunity, the median level of nCoV NTAb and nCoV S-RBD was increased by 5.26- and 8.03-fold, respectively. Consistent with the literature [25] , patients with CLD improve the humoral immune response after completing booster immunity, and the antibody level of patients with autoimmune hepatitis negative for nCoV S-RBD was increased by 148-fold [25] . Booster immunity prompted an immune response in liver transplant patients negative for nCoV S-RBD [23] .…”
Section: Discussionsupporting
confidence: 85%
“…Compared to the antibody level of primary immunity, the median level of nCoV NTAb and nCoV S-RBD was increased by 5.26- and 8.03-fold, respectively. Consistent with the literature [25] , patients with CLD improve the humoral immune response after completing booster immunity, and the antibody level of patients with autoimmune hepatitis negative for nCoV S-RBD was increased by 148-fold [25] . Booster immunity prompted an immune response in liver transplant patients negative for nCoV S-RBD [23] .…”
Section: Discussionsupporting
confidence: 85%
“…Seroconversion was achieved in all AIH patients and antibody levels were significantly increased, especially in those with low antibody titres after the second vaccine dose, but titres were still lower compared with healthy controls132 (figure 4A). However, the magnitude of spike-specific T cells did not increase compared with the second vaccine dose132 (figure 4A). Thus, these data may support the concept of a fourth vaccination in this patient population, as the booster vaccination significantly improved at least the antibody response in those patients with a weak immune response prior to the booster vaccination.…”
Section: Sars-cov-2 and The Adaptive Immune Responsementioning
confidence: 95%
“…Indeed, Hartl et al investigated the influence of a third mRNA-based or vector-based COVID-19 vaccination on the adaptive immune response in 81 AIH patients 132. Seroconversion was achieved in all AIH patients and antibody levels were significantly increased, especially in those with low antibody titres after the second vaccine dose, but titres were still lower compared with healthy controls132 (figure 4A). However, the magnitude of spike-specific T cells did not increase compared with the second vaccine dose132 (figure 4A).…”
Section: Sars-cov-2 and The Adaptive Immune Responsementioning
confidence: 99%
“…Davidov et al assessed immune responses in liver transplant recipients before and after the third dose of the BNT162b2mRNA vaccine and found that enhanced vaccination significantly increased the humoral immune response rate (56% vs. 98%) and the level of anti-S-RBD IgG and neutralizing antibodies [18] . Another study by Hartl et al confirmed a significant increase in the median S-RBD antibody levels in patients with autoimmune hepatitis (AIH) after the third COVID-19 vaccination [19] . However, these studies only included patients with liver transplantation and AIH, excluding patients with CLD, especially cirrhosis.…”
Section: Discussionmentioning
confidence: 89%
“…98%) and the level of anti-S-RBD IgG and neutralizing antibodies [18] . Another study by Hartl et al confirmed a significant increase in the median S-RBD antibody levels in patients with autoimmune hepatitis (AIH) after the third COVID-19 vaccination [19] . However, these studies only included patients with liver transplantation and AIH, excluding patients with CLD, especially cirrhosis.…”
Section: Discussionmentioning
confidence: 99%